The anticancer effects of curcumin and clinical research progress on its effects on esophageal cancer - Wang, Shimeng; Gao, Xinliang; Li, Jialin; Wei, Shixiong; Shao, Yifeng; Yin, Yipeng; Zhang, Duo; Tang, Mingbo (Frontiers in Pharmacology, 2022)
Esophageal cancer (EC) is a common tumor of the gastrointestinal system and a major threat to human health. The etiology and incidence of EC vary depending on the type of pathology. Owing to the unique physiological structure of the esophagus and the poor biological behavior of EC, the treatment modalities available are limited, and the prognosis of patients is relatively poor. Curcumin is a type of natural phytochemical belonging to the class of phenolic compounds. It exerts favorable anticancer effects on various cancers. A growing body of evidence indicates that curcumin suppresses tumor development and progression by inhibiting tumor cell proliferation, invasion, and migration, thus inducing apoptosis, regulating microRNA expression, reversing multidrug resistance, and inducing sensitivity to the therapeutic effect of chemoradiotherapy. Multiple cellular molecules, growth factors, and genes encoding proteins participating in different signaling pathways interact with each other to contribute to the complex and orderly anticancer effect. The efficacy and safety of curcumin have been established in preclinical studies for EC and clinical trials for other cancers. However, the low bioavailability of curcumin limits its clinical application. Therefore, the modification of curcumin analogs, the combination of curcumin with other drugs or therapies, and the use of novel nanocarriers have been widely investigated to improve the clinical effects of curcumin in EC.